The effect of ginkgo biloba extract in experimental strangulation ileus in a rat model - Adnan ŞAHİN and Ömer ÇOLAK and Özkan ALATAŞ and Cengiz BAYÇU and H. Ahmet KASAP and Bekir YAŞAR and Ertuğrul KARAHÜSEYİNOĞLU and Haluk KİPER (Turkish Journal of Gastroenterology, 2020)
-